Europe’s gift to the United Kingdom’s unwritten constitution – juridification - Young, A; Birkinshaw, P; Mitselegas, V; Christou, T (T.M.C. Asser Press, The Hague, 2019)
The United Kingdom constitution is the only uncodified constitution in Europe, and is described in the report as evolutionary, historical and predominantly political, responding piecemeal to developments through pragmatic solutions. A central concept is parliamentary sovereignty. The Supreme Court, replacing the Appellate Committee of the House of Lords, started its work in 2009; it can make a declaration of incompatibility with the ECHR, but has no power to annul legislation (although prior to Brexit, the courts were willing to disapply legislation which contravened directly effective provisions of EU law). Fundamental rights are predominantly protected by the Human Rights Act 1998, which incorporates the ECHR into UK law and the common law. A proactive role in raising fundamental rights issues, also in relation to EU law, is played by parliamentary scrutiny committees, NGOs and other institutions. These have contributed e.g. to the subsequent introduction of rights-based safeguards to European Arrest Warrant legislation and of a forum bar with regard to international extradition treaties. In terms of the main comparative influences, UK law is more likely to refer to the principles found in the common law of the US, Australia, Canada and New Zealand. Although European influences are present and have increased, it is unclear how far these influences will remain post Brexit. The report observes that membership of the EU and of the ECHR has helped to subject the UK constitution to juridification. In general, EU law has in many areas enhanced rights protection, e.g. as regards the right to privacy and the general principles of law; indeed, the latter were introduced into the UK through EU and ECHR law. The report does not address the Brexit process, although a brief post scriptum note has been added.